2020
DOI: 10.18632/aging.202292
|View full text |Cite
|
Sign up to set email alerts
|

High expression of RRM2 as an independent predictive factor of poor prognosis in patients with lung adenocarcinoma

Abstract: Ribonucleotide reductase subunit M2 may play a role as a potential prognostic biomarker in several cancers. In this study, we evaluated whether RRM2 gene expression is associated with the prognosis of patients with lung adenocarcinoma (LUAD) using publicly available data from The Cancer Genome Atlas (TCGA). Wilcoxon signed-rank test and logistic regression were performed to evaluate the association between RRM2 expression and clinical features in patients with LUAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 48 publications
2
74
0
Order By: Relevance
“…Ribonucleotide reductase M2 subunit (RRM2), a rate-limiting enzyme involved in DNA synthesis and damage repair, plays important roles in many cellular processes such as cell growth, invasiveness, migration and senescence et al [65]. RRM2 as a tumor driver is frequently overexpressed in various malignancies [66][67][68]. Others found that the expression level of RRM2 was correlated with invasion, cell differentiation, and metastasis in colorectal carcinoma [69], and correlated with lung cancer grade level [70].…”
Section: Discussionmentioning
confidence: 99%
“…Ribonucleotide reductase M2 subunit (RRM2), a rate-limiting enzyme involved in DNA synthesis and damage repair, plays important roles in many cellular processes such as cell growth, invasiveness, migration and senescence et al [65]. RRM2 as a tumor driver is frequently overexpressed in various malignancies [66][67][68]. Others found that the expression level of RRM2 was correlated with invasion, cell differentiation, and metastasis in colorectal carcinoma [69], and correlated with lung cancer grade level [70].…”
Section: Discussionmentioning
confidence: 99%
“…Current research reports that RRM2 is relatively highly expressed in breast cancer [17,18], lung adenocarcinoma (LUAD) [19,20], and cervical cancer [21,22], and it is also expressed in a variety of tumor cell proliferations. It plays an important role in the process of invasion, invasion and migration.Src kinase is the main product of the proto-oncogene c-Src and is a non-receptor tyrosine protein kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al recently revealed that RRM2 may prevent iron death in liver cancer and can be utilized as a tumor biomarker (34). In patients with lung adenocarcinoma, two investigations by Jin et al and Ma et al highlighted that the elevated RRM2 expression can be an independent predictor for poor prognosis (35,36). Through bioinformatics study, Shen et al discovered that RRM2 is substantially negatively associated with clinical staging in OC and that it represents an anticancer therapeutic target for patients with OC.…”
Section: Discussionmentioning
confidence: 99%